2016
DOI: 10.5830/cvja-2016-029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in pre-pubertal schoolchildren in Angola

Abstract: SummaryMethodsThe incidence of obesity is increasing worldwide, especially in countries with accelerated economic growth. We determined the prevalence of and associations between overweight/ obesity and cardiovascular risk factors in pre-pubertal (seven- to 11-year-old) schoolchildren (both genders, n = 198) in Luanda, Angola. Biochemical (fasting blood) and clinical examinations were obtained in a single visit. Data are reported as prevalence (95% confidence intervals) and association (r, Pearson).ResultsPrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
4
0
2
Order By: Relevance
“…In our group, 42.57% of children had a cholesterol level ≥ 170 mg/dL. Silva et al in 198 children from Angola aged 7-11 years also reported a high percentage of hypercholesterolemia -in 69.2% of participants [10]. In our group of children with abnormal lipid profile, a quarter were overweight, obese or hypertensive, but all were aged three years or over.…”
Section: Discussionsupporting
confidence: 43%
“…In our group, 42.57% of children had a cholesterol level ≥ 170 mg/dL. Silva et al in 198 children from Angola aged 7-11 years also reported a high percentage of hypercholesterolemia -in 69.2% of participants [10]. In our group of children with abnormal lipid profile, a quarter were overweight, obese or hypertensive, but all were aged three years or over.…”
Section: Discussionsupporting
confidence: 43%
“…Body mass index (BMI) values were adjusted for differences in gender and age using growth reference data for children and adolescents, 5–19 year- old [ 30 ]. Children whose BMI was less than the 5th percentile were considered underweight [ 31 ]. Following World Health Organization (WHO) guidelines, anaemia was defined as haemoglobin level of less than 11 g/dl [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study conducted among adolescent school children in the Eti-Osa Local Government Area of Lagos State, Nigeria, recorded that only 3.6 per cent of participants had TC greater than 200 mg/dL [18]. The highest prevalence of high TC among Angolan pre-pubertal adolescents, 7 to 11 years of age, was estimated to be 69.2% [19].…”
Section: Problem Of Dyslipidaemia In Childrenmentioning
confidence: 99%